IMPLICATIONS OF THE NEW LEGISLATION ON THE FUNDAMENTAL PRINCIPLES OF THE CRIMINAL TRIAL - Andrei ZARAFIU (Challenges of the Knowledge Society)
Each type of criminal trial is construed, from a systemic and normative perspective, on a range of fundamental rules. The current pattern of criminal trial applied at national level since the implementation of the New Code of Criminal Procedure knows the same normative approach, which begins with the regulation of the Principles for the application of the criminal procedure law. Even if, from the perspective of the form, the new procedure law was construed on the same normative fundament, from the perspective of the content, these differ from the previous regulations, being more adapted to the new legal realities and correspond to the trial model proposed by the new legislation. This study aims to analyse the new fundamental principles of the criminal trial, to identify the current dimension of their normative content and to appraise the way in which these reason with the warranties systems offered by the European regulations.